(13x+14)(6x-5)=0
78x²-65x+84x-70=0
78x²+19x-70=0
It was equation.
______________
Factoring⇒ a×c=78×(-70)=-5460
84×(-65)=-5460
84+(-65)=19 which is b
__________________
78x²+84x-65x-70=0
6x(13x+14)-5(13x+14)=0
(13x+14)(6x-5)=0
13x+14=0 6x-5=0
13x=-14 6x=5
x=-14/13 x=5/6
Two solution X=-14/13;5/6
I'm guessing you're asking what shape do you get if you cut a hexagon is cut into sixths.
If this hexagon is a regular hexagon, then the shapes would be equilateral triangles.
Answer:
p = -5
every element in the sequence is created by subtracting 3 from the pervious element.
Step-by-step explanation:
I am not sure you put every necessary information here.
but I'd the visible information is truly everything, then it's is trivial.
the difference between 4 and 1 is ... well, -3. meaning we subtract 3 from 4 to get 1.
we suspect this is the rule and keep trying.
1 -3 = -2
hey it works.
and -8 -3 = -11
hey, also correct.
and the difference between -2 and -8 is -6, and when we place another item in between (p), we cut that in half again to -3. so, it is all consistent.
therefore,
p = -2 -3 = -5
the rule is
an = an-1 - 3
a=1.34
b=ln-10
ln>10
Step-by-step explanation: